Membership categorisation and antagonistic Twitter formulations. Issue 6 (December 2017) - Housley, William; Webb, Helena; Edwards, Adam; Procter, Rob; Jirotka, Marina
During the course of this article, we examine the use of membership categorisation practices by a high-profile celebrity public social media account that has been understood to generate interest, attention and controversy across the UK (and wider European) media ecology. We utilise a data set of harvested tweets gathered from a high-profile public 'celebrity antagonist' in order to systematically identify types of antagonistic formulation that have generated different levels of interest within the social media community and beyond. Drawing from classic ethnomethodological studies of banner headlines and other means of generating public interest and 'making sense', we respecify high-profile antagonistic tweets as category formulations that exhibit particular and regular membership category features that are reflexively bound to potential antagonistic readings, interest and controversy. In conclusion, we consider how such formulations may be understood to represent resources that constitute ignition points within antagonistic flows of communication and information that can be metaphorically understood as 'digital wildfires'.